2016
DOI: 10.1111/izy.12127
|View full text |Cite
|
Sign up to set email alerts
|

Husbandry, management and breeding of the Greater one‐horned rhinoceros Rhinoceros unicornis at Zoo Basel

Abstract: As poaching incidents of rhinoceros species are continuously increasing in the wild, the need for zoological institutions to breed these charismatic species becomes ever more important. This article summarizes the knowledge gained about keeping, managing and breeding Greater one‐horned rhinoceros Rhinoceros unicornis at Zoo Basel, Switzerland, over the past 15 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…A diet based on grass hay (possibly mixed with straw) of a low nutritional quality, with a restricted small proportion of a pelleted compound feed (to ensure mainly mineral, but not energy provision), and a possible addition of browse, in the form of branches, is probably the best diet recommendation from both an enrichment and a health point of view [Clauss and Hatt, ]. Consultation of the feeding guidelines mentioned in the EAZA best practice guidelines [von Houwald, ] is strongly recommended.…”
Section: Discussionmentioning
confidence: 99%
“…A diet based on grass hay (possibly mixed with straw) of a low nutritional quality, with a restricted small proportion of a pelleted compound feed (to ensure mainly mineral, but not energy provision), and a possible addition of browse, in the form of branches, is probably the best diet recommendation from both an enrichment and a health point of view [Clauss and Hatt, ]. Consultation of the feeding guidelines mentioned in the EAZA best practice guidelines [von Houwald, ] is strongly recommended.…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, the new indoor stables and outdoor enclosures were finished, and the substrate used for both inside and outside consists of a 50 cm‐deep untreated wood‐chip layer (von Houwald, ). This material is bouncy, easily replaced and can also be eaten or played with.…”
Section: Prevention Of Foot Problemsmentioning
confidence: 99%
“…Considering that large mammals' feet support their body mass during gait, understanding healthy foot function is important for understanding healthy gait. This is particularly imperative in view of documented rhinoceros foot pathologies (Dudley et al, 2014;Flach et al, 2003;Galateanu et al, 2013;Harrison et al, 2011;Jacobsen, 2002;Jones, 1979;Regnault et al, 2013;Von Houwold, 2001;Von Houwald and Guldenschuh, 2002;Von Houwold and Flach, 1998;Zainuddin et al, 1990). Previous research on museum specimens found a high occurrence of enthesopathies and osteoarthritis on the phalanges of rhinoceros feet (Regnault et al, 2013)--of the 81 feet from 27 rhinoceroses studied, 54 feet from 22 individuals exhibited osteopathologies (Dudley et al, 2014).…”
Section: Introductionmentioning
confidence: 99%